2020
DOI: 10.5617/adno.7909
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Rating Scales to Assess Writing Proficiency Development in Young Learners

Abstract: Writing assessment scales were developed to include functional aspects of writing proficiency in contemporary Norwegian teaching toolkits for Grades 1 to 3. This study aims to describe the process of developing empirically based, assessor-oriented writing proficiency scales and of investigating the quality of the scales. We focus on psychometric qualities, professional users’ perceptions of their quality, and the teachers’ use of the scales. Overall, the first piloted version of the scales showed indications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Each trait was scored using a separate 1 to 5 rating scale. The rating scaled were developed and validated for use in Grades 1–3 by Skar, Jølle, and Aasen (2020), and also used in Skar et al (2021), who reported that, on average, girls outperformed boys, and students in higher grades outperformed students in lower grades. Higher scores represented better quality for the trait assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Each trait was scored using a separate 1 to 5 rating scale. The rating scaled were developed and validated for use in Grades 1–3 by Skar, Jølle, and Aasen (2020), and also used in Skar et al (2021), who reported that, on average, girls outperformed boys, and students in higher grades outperformed students in lower grades. Higher scores represented better quality for the trait assessed.…”
Section: Methodsmentioning
confidence: 99%
“…As an example, consider audience awareness which targeted the extent to which a text not only communicated with the reader, but also if the young author had managed to decontextualize his/her writing enough for a reader to make meaning of the content even if the reader was unable to clarify content in interviews with the author (Skar, Aasen et al, 2022 ). Prior to this investigation, the rating scales had been validated (Skar, Jølle, et al, 2020 ) and used to assess thousands of texts (Ska, Lei, et al 2022 ). Please refer to Appendix A in Skar, Kvistad, et al ( 2022 ) for descriptors for all eight scales.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, there is currently a lack of knowledge concerning these areas. To meet these challenges and to provide the sector and teacher education with relevant knowledge, the FUS project's primary objective is to investigate the consequences of an early start with functional writing on young students' writing proficiency (see Skar et al, 2020 for construct definitions), teachers' professional learning, and learning activities.…”
Section: Background and Study Aimsmentioning
confidence: 99%
“…To measure text quality, a new assessment tool (Skar et al, 2020), which in a validating phase produced reliability well over .85, was developed. All texts will be rated on eight rating scales (Audience Awareness, Vocabulary, Organization of Content, Language Use, Punctuation, Spelling, Handwriting, and Relevance), and all assessments will be processed using contemporary statistical techniques in writing assessment (i.e., many-facet Rasch measurement; Skar, 2017).…”
Section: Premeasures and Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation